2013
DOI: 10.24908/pceea.v0i0.4850
|View full text |Cite
|
Sign up to set email alerts
|

Creating Faculty Buy-In: Leadership Challenges in Implementing Ceab Graduate Attributes

Abstract: -In 2009 the Canadian EngineeringAccreditation Board (CEAB)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Since the 1989 Washington Accord (International Engineering Alliance [IEA], 2015), engineering education programs accredited by signatories, such as CEAB and the American Accreditation Board for Engineering and Technology (ABET), are recognized as academically equivalent to support international mobility for professional engineers. In 2009, the Washington Accord accrediting bodies introduced the engineering graduate competency-based outcomes as part of the accreditation process (Easa, 2013;Frank et al, 2011;Gopakumar et al, 2013;Stiver et al, 2010). Subsequently, engineering programs began grappling with how these graduate attributes would become a part of the accreditation process with limited direction from the Canadian Engineering Accreditation Board or Washington Accord signatories.…”
Section: Prior Research On Implementing Graduate Attributesmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the 1989 Washington Accord (International Engineering Alliance [IEA], 2015), engineering education programs accredited by signatories, such as CEAB and the American Accreditation Board for Engineering and Technology (ABET), are recognized as academically equivalent to support international mobility for professional engineers. In 2009, the Washington Accord accrediting bodies introduced the engineering graduate competency-based outcomes as part of the accreditation process (Easa, 2013;Frank et al, 2011;Gopakumar et al, 2013;Stiver et al, 2010). Subsequently, engineering programs began grappling with how these graduate attributes would become a part of the accreditation process with limited direction from the Canadian Engineering Accreditation Board or Washington Accord signatories.…”
Section: Prior Research On Implementing Graduate Attributesmentioning
confidence: 99%
“…3 The International Engineering Alliance (IEA) is a non-profit organization that establishes and enforces international standards for engineering education to ensure quality and mobility. 4 Queen's University, the University of Calgary, UBC, the University of Toronto, Dalhousie, and the University of Guelph (Frank et al, 2011;Kaupp et al, 2012;Kaupp & Frank, 2016;Stiver et al, 2010;Stiver, 2011), Ryerson University (Easa, 2013;Salustri & Neumann, 2016;Shehata & Schwartz, 2015), Concordia University (Gopakumar et al, 2013;Hamou-Lhadj et al, 2015), the University of Manitoba (Seniuk-Cicek et al, 2014;Sepheri, 2013), the University of Alberta (Dew et al, 2013;ElAtia & Ipperciel, 2015a, 2015bElAtia et al, 2016;ElAtia et al, 2020;Ivey, 2017;Ivey et al, 2018;Parker et al, 2019;Watson et al, 2018), the University of Victoria (Gwyn, 2016(Gwyn, , 2017Gwyn & Gupta, 2015), and Memorial University (Spracklin-Reid & Fisher, 2012…”
Section: Contact Informationmentioning
confidence: 99%
“…Impact on Faculty-It was suggested that faculty resistance to adopting graduate attributes might stem from the imposition by an outside agency, namely the CEAB [26]. Such would result in skepticism and disinterest in the process of curricular evaluation and change [78]. Resistance to change was attributed to a culture of autonomy that exists at academic institutions, and onus was placed on those in leadership positions to acknowledge and consider this phenomenon with patience and perseverance [78].…”
Section: Concerns and Issuesmentioning
confidence: 99%
“…Such would result in skepticism and disinterest in the process of curricular evaluation and change [78]. Resistance to change was attributed to a culture of autonomy that exists at academic institutions, and onus was placed on those in leadership positions to acknowledge and consider this phenomenon with patience and perseverance [78]. One paper explained that the culture of autonomy and academic freedom has a positive effect on student learning and should be supported during development of an outcomes-based curriculum [79].…”
Section: Concerns and Issuesmentioning
confidence: 99%
“…Faculty member buy-in is not an insignificant issue: as Gopakumar et al [10] note, engineering schools across the country face significant challenges in incorporating attributes-based outcomes assessment. In particular, it is difficult to engage faculty the CA/GA process, let alone make them accountable for program-wide continual improvement.…”
Section: Classroom Assessmentmentioning
confidence: 99%